Pertanggungjawaban Pidana Kepada Pelaku Pengedaran Obat Sirup Anak yang Mengakibatkan Acute Kidney Injury (AKI) - Aritonang, Agnes Monica; Saragih, Mario Setiabudi; Hasibuan, Rizky Maulana (JURNAL LEGISIA, 2024)
Every action we take has its own consequences for ourselves and the people around us, this is like a "business actor" in carrying out his business activities who expects economic consequences for his business in the form of profit obtained from the sale of the products they produce. however, business actors must not forget the standards set by the relevant supervisory parties, so that the results of the goods / services they market can meet consumer needs and satisfy the consumers themselves. for example, a drug business that is required to include a production code, expiration date, composition, and so on. if one thing is not fulfilled by the business actor, the relevant agency in this case BPOM can withdraw the distribution permit and stop the production and marketing of the drug. If one of the things is not fulfilled by the business actor, the relevant agency in this case BPOM can withdraw the distribution permit and stop the production and marketing of these drugs, a real example that is currently in the news is the case of Acuted Kidney Injury (AKI) or what we know as Acute Kidney Failure which is included in the collection of extraordinary cases that occur in Indonesia because it takes many lives, from this event it was found that negligence in producing drugs in the form of a substance whose cadation exceeded the limit allowed by BPOM. as a result, there is a lot of gossip about the case. As a result, there is a lot of gossip among citizens about the forms of criminal liability of the perpetrators of criminal acts in this case the unscrupulous businessman of the children's syrup medicine, so that the victims get their rights in the form of compensation and compensation. In this case, the government as the supervisor and guarantor of medicines and food through BPOM is also highlighted regarding their supervisory performance, because drugs that are alleged to have mixed substances that exceed the safe threshold actually escape the supervision of related parties and even have production permits and distribution permits listed on the packaging label of the children's syrup medicine.